The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species - Lin, James; Shao, Kwang-Tsao; Smith, David G. (Zootaxa, 2018)
The congrid eel genus Macrocephenchelys in Taiwan is reviewed. Three species are recognized. Macrocephenchelys brachialis was originally described from Indonesia and is also known from Taiwan, Madagascar, and Vanuatu; it is common in Taiwan but known from few specimens elsewhere. Macrocephenchelys brevirostris was described from Taiwan, where it is common; its occurrence outside Taiwan is uncertain. Macrocephenchelys nigriventris sp. nov. is described here from 28 specimens collected in Taiwan. Macrocephenchelys brachialis is distinguished from the other two species by its more elongate body, more posterior dorsal-fin origin (behind tip of pectoral fin), shorter head (less than 10% total length), presence of a supratemporal pore, absence of fleshy papillae dorsally on the head, absence of sensory pits on the abdomen, and more than 170 vertebrae. Macrocephenchelys nigriventris is distinguished from M. brevirostris by the presence of a patch of black pigment around the anus and adjacent abdomen (absent in M. brevirostris), preanal length 24–28% total length (27–34% in M. nigriventris), and 128–135 vertebrae (147–154 in M. brevirostris). The only other species currently recognized is M. soela from Australia; it is distinguished from all the others by the more anterior origin of the dorsal fin, over the middle of the pectoral fin (vs. over or behind the tip of the pectoral fin).